Nothing is destroyed, everything is transformed: the enforceability of the obligation to repair in the framework of a succession of States - Vergara Lamadrid, Ana Paola (2022)
The constant politicization of the succession of States has been a problem when regulating how to regulate its effects. In the first codifying attempts, international responsibility was not ddressed as part of the study on the effects of this phenomenon. However, thanks to the wide acceptance of the work of the International Law Commission of the United Nations in its work on the international responsibility of the State, it is no longer possible to invoke the succession of States to undermine the enforceability of the obligation to repair that has arising out of the commission of an internationally wrongful act. This dogmatic change will provide more light for an eventual regulation of the subject under analysis, but it could also be useful for the constant claims of States that, in their past life, were colonies where atrocities were perpetuated.